Cooperative hand movements: effect of a reduced afference on the neural coupling mechanism. Issue 8 (23rd May 2018) - Thomas, Felix A.; Dietz, Volker; Scharfenberger, Thiemo; Schrafl-Altermatt, Miriam
Abstract : The aim of this study was to evaluate the influence of unilateral reduction of afferent input on the 'neural coupling' mechanism during cooperative hand movements. This 'neural coupling' is reflected in the task-specific appearance of contralateral reflex responses in forearm muscles to unilateral arm nerve stimulation. Sensory input from the right hand was reduced by ischemic nerve block at the right wrist. Ipsilateral and contralateral reflex responses elicited by stimulation of the ulnar nerve either at the left or the right wrist proximal to the nerve block were recorded in forearm extensors during the performance of cooperative hand movements. During ischemia of the right hand, a significant difference was found in the magnitude of the contralateral responses, that is, contralateral reflex responses in the right arm were significantly higher compared with the left arm ( P =0.04). Ipsilateral reflex responses were not affected by ischemic nerve block. The reduced afference from the ischemic hand during cooperative hand movements is assumed to weaken the activity in ipsilateral pathways involved in the neural coupling mechanism. Consequently, a shift in the interhemispheric balance might lead to the relative increase and decrease in the contralateral responses to left and right nerve stimulation, respectively. The study provides novel information on the involvement of ipsilateral hemispheres in the performance of cooperative hand movements.